Hot-water rescue ice drilling system to recover subglacial lake exploring sonde: General concept - Liu, An; Fan, Xiaopeng; Talalay, Pavel; Wang, Rusheng; Li, Xiao (Polar Science, 2023)
Autonomous sondes are used to study the Antarctic subglacial environment, yet they risk of being frozen in ice due to heating failure. To recover an accidently frozen sonde this paper describes a concept for a hot-water rescue ice drilling system. A special hot-water drill tool was designed to drill downward along the cable/sonde and melt surrounding ice. Theoretical estimation indicated the power system needed to provide hot water at a flow rate of 25 L/min and a pressure of more than 4.2 MPa to release the sonde at ice depth of 500 m. Laboratory testing and field testing near the Chinese Zhongshan Station in Antarctica demonstrated rationality of the concept. Potential risks were estimated and corresponding solutions presented. The hot-water rescue ice drilling system mentioned in the paper provides a safety guarantee for subglacial lake successful exploration, furthermore supports more ideas for future ice sheet exploration. journal article